Rupture of Anastomotic Pseudoaneurysm of Brachiocephalic Arteriovenous Fistula: A Case from West Java - Rifqi Raihan Haris; Prasetyo Edi (JURNAL WIDYA MEDIKA, 2020)
Background: Post-traumatic pseudo aneurysm development is very rare in the peripheral arteries and is generally a late sequela of trauma. Their diagnosis and surgical treatment are extremely important, because they can cause severe disability, including loss of upper extremity and hand. Objective: To describe the clinical presentation, intervention, and outcome of ruptured anastomotic pseudoaneurysm of brachiocephalic arteriovenous fistula which has undergone surgical procedure. Methods: A 29-years-old man presented with arm swelling and extreme pain in his right arm since 3 days ago. He had undergone AVF procedure 3 weeks ago. His right arm was accidentally squeezed by his mother 1 week after surgery had been done. This patient underwent operation with general anesthesia. Proximal control was taken by tourniquet that maintained to inflate at 300 mmHg. The brachial artery is repaired using great saphenous vein patch plasty. Results: Patient’s postoperative course went well and there was no sign of complication, such as ischemia. Arm swelling were reduced after 2 weeks follow up. Conclusion: In our center, most of the cases of brachiocephalic AVF pseudoaneurysm are caused by trauma. MSCT angiography is sufficient for the diagnosis of this anomaly. All cases were managed by open surgery and resulted a good outcome.